Evaluation of an Interprofessional Student–Faculty Collaborative Clinic in a Jail. (October 2019) - Simon, Lisa; Beckmann, David; Reidy, Patricia; Cohen, Marya; Tobey, Matthew
Jail-based student-run clinics, though uncommon, have the potential to impact the future health workforce. We evaluated, via a survey of student attitudes and a collection of lessons learned, a student–faculty collaborative clinic that was implemented in a jail in 2015. Clinic participation led to significantly greater student volunteer ratings of the importance of collaborating with oral health providers and of comfort in providing care to incarcerated populations. We report lessons learned regarding logistical considerations, volunteer behavior, and common issues arising in clinic visits. The clinic proved feasible and sustainable over several years, offering a new model for the involvement of trainees in correctional health care.